2022
DOI: 10.1038/s41598-022-22984-6
|View full text |Cite
|
Sign up to set email alerts
|

DeepPDT-Net: predicting the outcome of photodynamic therapy for chronic central serous chorioretinopathy using two-stage multimodal transfer learning

Abstract: Central serous chorioretinopathy (CSC), characterized by serous detachment of the macular retina, can cause permanent vision loss in the chronic course. Chronic CSC is generally treated with photodynamic therapy (PDT), which is costly and quite invasive, and the results are unpredictable. In a retrospective case–control study design, we developed a two-stage deep learning model to predict 1-year outcome of PDT using initial multimodal clinical data. The training dataset included 166 eyes with chronic CSC and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Interestingly, despite overall thickness reduction, the choroidal vascular index is not affected by the procedure. Good responders to PDT have higher choroidal thickness compared to nonresponders 69 , 97 , 98 . This finding is also reflected in a study by Arrigo et al, which differentiate CSCR forms into RPE and choroidal subtypes 99 .…”
Section: Resultsmentioning
confidence: 95%
“…Interestingly, despite overall thickness reduction, the choroidal vascular index is not affected by the procedure. Good responders to PDT have higher choroidal thickness compared to nonresponders 69 , 97 , 98 . This finding is also reflected in a study by Arrigo et al, which differentiate CSCR forms into RPE and choroidal subtypes 99 .…”
Section: Resultsmentioning
confidence: 95%
“…Transfer learning method Field of research [17] Simple deep learning network on ImageNet Transfer learning generalizability test for multiple datasets in the image classification domain [18] Xception network pretrain on ImageNet Fingerprint recognition [19] Combining the Xception network pre-trained on imagenet with the designed function block Diagnosis of rectal cancer [20] Different pre-training methods on ImageNet Diabetic retinopathy fundus image classification [21] Pre-trained deep learning networks on the same type of dataset Pediatric pneumonia diagnosis [7] Two-stage transfer learning strategy Central serous chorioretinopathy (CSC) images classification.…”
Section: Studymentioning
confidence: 99%
“…(3) Medium size dataset of same data type: researchers found that transfer learning on medium size datasets of the same type can effectly enhances the network's ability to extract upper-level features. (4) Two-stage transfer learning: in recent years, researchers have combined above transfer learning methods and proposed two-stage transfer learning algorithms, such as [6][7][8][9].This technique can extract more effective features and obtain more accurate results.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, a model trained on large-scale genome data was first adapted for a small ethnic group through fine-tuning and additional domain adaptation training [ 9 ]. Thus, a new task with a small adaptation dataset can be trained using pre-trained weights from a large dataset through transfer learning [ 10 ]. It is expected that the spread of AI models for various groups will become possible through intra-study adaptation training using ocular images.…”
Section: Introductionmentioning
confidence: 99%